Brazils Highway BR-319: The road to the collapse of the Amazon and the violation of indigenous rights - Ferrante, Lucas; Bento Trindade de Andrade, Maryane; Leite, Luciana; Antonio Silva Junior, Carlos; Lima, Mendelson; Geraldo Coelho Junior, Marcondes; Carvalho da Silva Neto, Eduardo; Campolina, Daniela; Carolino, Katia; Maria Diele-Viegas, Luisa; Johnson de Area Leão Pereira, Eder; Martin Fearnside, Philip (DIE ERDE – Journal of the Geographical Society of Berlin, 2021)
One of the greatest threats to the Brazilian Amazon is the reconstruction and paving of the formerly abandoned Highway BR-319, which would link one of the most conserved blocks in the Amazon forest to the “arc of deforestation” on the southern edge of the region where most forest has already been destroyed. BR-319 and its planned side roads would allow the actors and processes from the arc of deforestation to move into vast areas of unprotected rainforest. In the specific case of this highway, a judicial decision that is not subject to further appeal established that environmental studies for the first section of the highway to be reconstructed (“Lot C”) must be carried out before paving. The federal highway department and the “Civil House” of President Bolsonaro’s presidential office ignored this decision and issued a call for bids for the construction work. Due to the current lack of governance in the BR-319 area and the history of deforestation whenever Amazonian highways are built, the decision on whether to suspend the contract for the “Lot C” is critical for the maintenance of both the ecosystem services of the Amazon forest and the way of life of indigenous and riverside people. This decision is expected to be made shortly by a single person.